Analysis, Design, Development, Implementation, and Evaluation of a Serious Game Designed to Inform Users on Environmental Issues - Alcid, Argomer S.; Bandril, Leonard Benjamin P.; De Guzman, Anfernee E.; Lopez, Lance Jasper C. (International Journal of Computing Sciences Research, 2017)
Purpose   – This study presented the results of each stage of the analysis, design, development, implementation, and evaluation (ADDIE) of a game designed to inform users on environmental issues. The game was named “Juan’s Kart” that aimed to teach players about waste segregation. Method – The analysis phase involved the conceptualization of a game and the determination of its design dimension. The design phase entailed development of game design guidelines, identification of hardware and software requirements specifications, and actual development of the game. The developed game was uploaded in Google Play. Four hundred respondents evaluated the game. Results – The game received favorable ratings from the respondents. Contributions – Thus, the game was successfully developed. It may be utilized as a training tool and its effectiveness may be investigated. Research Implications – Recommendations to improve the game were also presented.